Uptake of Europium(III) from Water using Magnetite Nanoparticles. (25th January 2016) - Carvalho, Rui Silva; Daniel‐da‐Silva, Ana L.; Trindade, Tito
Abstract : It is demonstrated that colloidal magnetite nanoparticles can be used as nanosorbents for lanthanide ions dissolved in water. In particular, a series of experiments are performed for the removal of Eu(III) in distinct analytical conditions and by applying an external magnet to collect the sorbents previously dispersed in water samples. Furthermore, strategies for surface chemistry functionalization are also investigated, aiming to investigate the effect of this parameter on the removal capacity of the Fe3 O4 nanoparticles. The supernatant solutions are monitored for the remaining amount of Eu(III) by fluorescence emission measurements in the presence of 2, 6‐pyridinedicarboxylic acid as a sensitizer. The results demonstrate that neat Fe3 O4 nanoparticles are capable of capturing lanthanide ions (III) from aqueous solutions (pH 7), without need of surface modification, and for subsequent removal by magnetic separation. During the removal, efficiency is increased after modifying the particles' surfaces with silica and 3‐aminopropyltrimethoxysilane; in alkaline medium (pH 10), there is complete removal regardless the type of nanosorbent used. This has been explained by the formation of insoluble Eu(III) species that adsorb strongly to the nanosorbents surfaces allowing their subsequent magnetic separation. Abstract : Magnetite and surface‐functionalized magnetite particles are used as nanoadsorbents for the uptake of Eu(III) dissolved in water samples. The nanoadsorbents are easily collected by magnetic separation and show an efficiency dependent on the type of surface functionalization and solution pH.